2020
DOI: 10.1213/ane.0000000000005211
|View full text |Cite
|
Sign up to set email alerts
|

Adult Emergence Agitation: A Veteran-Focused Narrative Review

Abstract: Emergence agitation (EA) is a self-limited state of psychomotor excitement during awakening from general anesthesia. EA is confined to the emergence period as consciousness is restored, which sharply distinguishes it from other postoperative delirium states. Sporadic episodes of EA may become violent with the potential for harm to both patients and caregivers, but the long-term consequences of such events are not fully understood. Current literature on EA in adults is limited to small-scale studies with incons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 84 publications
0
47
0
Order By: Relevance
“…After alignment of the metabolites with the MS database and screening, 31 significantly altered metabolites were selected to analyze the different metabolite patterns between the EA group and the non-EA group ( Table 3 ). The differentially regulated metabolites were classified into several “superclasses”: “Lipids and lipid-like molecules” (11 metabolites), “Organoheterocyclic compounds” ( Kanaya, 2016 ), “Organic acids and derivatives” ( Munk et al, 2016 ), “Nucleosides, nucleotides, and analogs” ( Wei et al, 2020 ), “Organic oxygen compounds” ( Wei et al, 2020 ), “Organic nitrogen compounds” ( Tolly et al, 2020 ), “Phenylpropanoids and polyketides” ( Tolly et al, 2020 ), and “Alkaloids and derivatives” ( Tolly et al, 2020 ). After alignment with the KEGG and MetaboAnalyst databases, altered metabolites were found to participate mainly in “purine metabolism,” “glycerophospholipid metabolism and nicotinate,” and “nicotinamide metabolism pathways.” We also analyzed the pathway enrichment of the 31 significantly altered metabolites, and 14 KEGG pathways were included ( Figure 4 ), which were mainly associated with “Glycerophospholipid metabolism,” “Phenylalanine, yrosine, and tryptophan biosynthesis,” and “Phenylalanine metabolism” ( Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After alignment of the metabolites with the MS database and screening, 31 significantly altered metabolites were selected to analyze the different metabolite patterns between the EA group and the non-EA group ( Table 3 ). The differentially regulated metabolites were classified into several “superclasses”: “Lipids and lipid-like molecules” (11 metabolites), “Organoheterocyclic compounds” ( Kanaya, 2016 ), “Organic acids and derivatives” ( Munk et al, 2016 ), “Nucleosides, nucleotides, and analogs” ( Wei et al, 2020 ), “Organic oxygen compounds” ( Wei et al, 2020 ), “Organic nitrogen compounds” ( Tolly et al, 2020 ), “Phenylpropanoids and polyketides” ( Tolly et al, 2020 ), and “Alkaloids and derivatives” ( Tolly et al, 2020 ). After alignment with the KEGG and MetaboAnalyst databases, altered metabolites were found to participate mainly in “purine metabolism,” “glycerophospholipid metabolism and nicotinate,” and “nicotinamide metabolism pathways.” We also analyzed the pathway enrichment of the 31 significantly altered metabolites, and 14 KEGG pathways were included ( Figure 4 ), which were mainly associated with “Glycerophospholipid metabolism,” “Phenylalanine, yrosine, and tryptophan biosynthesis,” and “Phenylalanine metabolism” ( Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of EA pathogenesis is not known. A common hypothesis is that excessive reactions may occur due to internal or external stimuli as consciousness returns during the recovery from anesthesia ( Brown et al, 2010 ; Tolly et al, 2020 ). It has been reported that several factors contribute to EA occurrence, including preoperative concomitant diseases and excessive sympathetic activation ( Kim et al, 2019 ) from indwelling catheters and tubes ( Kwon et al, 2016 ; Fields et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 In a majority of literature, the condition is referred to as emergence delirium, agitation, or excitation. 2,3 The condition often begins with awakening or emergence from the anesthetic and/or adjunct agent and is followed by a return to baseline behavior after a short time period (typically less than 30 minutes). [2][3][4][5][6] During the bout of delirium/agitation, the patient may engage in a wide range of behavior that includes one or more of the following: violence (e.g., punching, kicking, hitting, biting), thrashing movement, aggression, combativeness, screaming, disconnect with current time and place (e.g., flashbacks, hallucinating, disoriented), attempting to exit bed/table, and attempting to remove medical apparatuses.…”
Section: Introductionmentioning
confidence: 99%